The Effect of Growth Assets, Earning Per Share, Leverage, Return on Investment, Yield Dividend on Share Return of Go-Public Banking Companies, 2012 – 2017 - N Hidayati; MAB Hartono (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
In the investment sector, there is a familiar topic to discuss, there are various kinds of views and theories related to investment. Investments can be made through various means and media. One form of investment that is commonly carried out is through the media of shares in a company. When investing, investors expect a return on that investment. The yield in the form of shares is dividend income and an increase in the value of the shares if the shares are marketed on the stock exchange floor. The calculation of the increase in share prices depends on the performance of a company in generating profits in its operational activities. One way to evaluate company activities in making a profit is by analyzing the company's financial ratios. In this study, the author wants to describe the return of a banking stock to the variables of financial ratio analysis whether it will give a significant influence on the company's stock returns. The purpose of this research is to describe to users, the impacts and effects that need to be considered for investing in order to get the expected results. Based on the results of data testing and discussion of research results on the effect of asset growth, earning per share, leverage, Return on Investment, and dividend yield on stock returns in banking companies listed on the Indonesia Stock Exchange, asset growth does not significantly affect stocks return, earning per share has a significant effect on stock returns, leverage has no significant effect on stock returns, Return on Investment has no significant effect on stock returns, the dividend yield has an insignificant effect on stock returns.